Gypsum amendment and seasonal variability: effect on soil quality, fruit characteristics and toxicological responses of Cucumber (Cucumis sativus l.) in the Ahafo-Kenyasi Mining Area of Ghana - Onwona-Hwesofour Asante, Kwaku; Abugri, Simon; Derkyi, Nana Sarfo Agyemang (World Journal of Advanced Research and Reviews, 2021)
Depending on soil, climate and crop characteristics exposed subsoils can be amended with gypsum for agricultural activities when topsoil is inadequate as a result of natural and geophysical activities. To determine how exposed subsoil amendment with gypsum interact with weather patterns to influence soil chemical properties, cucumber growth, fruit characteristics and heavy metal concentration, a two-seasonal experiment was conducted in the major and minor rainy season of 2020 in the Ahafo-Kenyasi Mining Area in Ghana. The experiment was laid out as a 6x2 factorial arranged in randomized complete block design, consisting of 6 gypsum application rates (20 ton/ha, 40 ton/ha, 60 ton/ha, 80 ton/ha, 0 ton/ha (subsoil control) and 0 ton/ha (topsoil control)) in two rainy seasons and replicated three times. The results show that gypsum application and rainy seasons interact to significantly influence soil chemical properties, cucumber growth and fruit characteristics. Increasing gypsum application resulted in decreased organic carbon, increased calcium, increased available P, increased exchangeable magnesium (Mg), increased pH during both major and minor rainy seasons. Vine length, number of leaves, number of fruits per plant and fruit weight of cucumber were increased with increasing gypsum application during the minor rainy season. In spite of exceeding permissible limits in soils and crops, arsenic (As), cadmium (Cd) and mercury (Hg) showed similar concentrations (below 2 mg/kg) in cucumber during the minor and major rainy seasons across gypsum treatments. Lead (Pb) concentration in cucumber was significantly higher in the major season across treatments. There was no difference in lead (Pb) concentration for treated vs untreated, and no increase across the amendment range. Further studies on how heavy metals in soil and plants interact with plant phytochemicals in ecosystems and living tissues are recommended
Keywords: Sustainable mining; Circular economy; Gypsum; Seasonal variability; Heavy metal toxicology; Daniel Sarfo Akoto; ACE: Energy and Environmental Sustainability; RCEES; Ghana; Power; University of Energy & Natural Resources